Coronary angiographic assessment of streptokinase efficacy in young patients with ST-elevation myocardial infarction - Chetan Solanki; Kuwer Devi Singh; Sunil Kumar Tripathi; Manoj Indurkar; Rakesh Kumar Tikadar (Asian Journal of Medical Sciences)
Background: Thrombolytic therapy has emerged as one of the most effective interventions for acute myocardial infarction, a condition that is the leading cause of mortality worldwide.